Study of the Safety and Toxicokinetic Parameters of the Drug Eladis® in Preclinical Trials with Repeated Administration - A. A. Matichin; M. V. Miroshnikov; A. A. Matichina; V. M. Kosman; M. V. Karlina; E. M. Petrova; A. A. Globenko; E. A. Jain; A. V. Kapashin; A. L. Vladykin; A. S. Kolosov; M. A. Pasko (Антибиотики и Химиотерапия)
Cough is one of the most common reasons for initial visits to healthcare providers, affecting 40–50% of patients with viral respiratory tract infections. Treatment options for cough include medications that block signal transmission at the central or peripheral level of the reflex arc, as well as mucolytic and expectorant agents. Valenta Pharm JSC has developed an innovative drug, Eladis® (film-coated tablets, 20 mg and 40 mg), intended for the treatment of cough in patients with acute respiratory infections. The aim of the present study was to assess the safety profile and toxicokinetic parameters of the drug after repeated administrations. In the study conducted on mature rabbits, the drug was administered orally at doses of 1, 3, or 6 tablets/animal over 28 days, corresponding to 13.3, 40, and 80 mg/kg, respectively. No signs of intoxication were observed in any of the experimental groups. To evaluate toxicokinetic parameters, blood samples were collected from the marginal ear vein after the 1st and 28th days of administration. Both single and multiple (28-day) administrations of the drug showed a statistically significant increase in Cmax and AUC0–24 with increasing doses. No drug accumulation was observed following repeated administration on day 28. In a separate study on juvenile rats, Eladis® was administered intragastrically for 30 days at doses of 11.8, 118, and 236 mg/kg. The results indicated no significant effects of the drug on body weight gain, animal behavior in a battery of functional tests, as well as the estimated physiological, biochemical, and hematological parameters. The drug demonstrated no local irritant or immunotoxic effects and had no impact on spermatogenesis.